Keragaman dan Kelimpahan Plankton di Perairan Rawa Pening Ambarawa Kabupaten Semarang - Widya Asmara, Yovita; Sih P, Agatha; Nugroho W, Dwi (Jurnal Farmasi (Journal of Pharmacy), 2014)
The existence of organic and inorganic materials which come from river, food waste, fish metabolism waste, and aquatic macrophyte decomposed waste could become the source of nutrient. One of organism which life in Rawa Pening Ambarawa is plankton that can be used to evaluate community stability on waters by investigate it diversity and abundance. The research to know the diversity and abundance of waters plankton at Rawa Pening, Ambarawa, Central Java has been conducted from July to September 2006. The research site used a survey the sample were taken and the sampling sites were divided into 3 zones (inlet, middle, and outlet zones), with 3 stations on each zone. The parameters were the number of species and individual. The supporting parameters were water physical chemistry of Rawa Pening. The data were analyzed using descriptive analysis and 50% rules. Result of research showed that the diversity of plankton which found in inlet zone counted as 30 genera with plankton abundance 2,227 ind/l, in middle zone counted as 31 genera with plankton abundance 2,753 ind/l, and in outlet zone counted as 29 genera with plankton abundance 1,215 ind/l. Based on the result, the diversity and abundance of plankton in inlet, middle, and outlet zones is spread evenly.